1986
DOI: 10.1111/j.1475-6803.1986.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of Sinking Funds on Bond Risk Premia

Abstract: This study analyzes the effect that two options created by the inclusion of a sinking fund clause in a bond indenture have on the bond issue's secondary market risk premium. The impact of market prices that exceed current sinking fund redemption prices, and of par versus premium redemption, is clearly apparent when a set of issue-specific and macroeconomic control variables are incorporated into a model of bond risk premia. Thus. secondary market prices for the large-volume utility bond transactions in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…On October 4, 1979, the Federal Reserve Board announced that monetary policy would focus on monetary aggregates, with consideration of interest rates relegated to second place. A significant effect of this policy change on bond risk premia is demonstrated by Barrett, Heuson, and Kolb [1] and a significant effect on Treasury bond option premia is shown by Jordan, Seale, and Barnhill [12]. The same policy change is examined in the present study and is shown to have a significant impact on sinking fund preferred stock.…”
Section: Preferred Stock—with and Without Sinking Fundssupporting
confidence: 64%
See 4 more Smart Citations
“…On October 4, 1979, the Federal Reserve Board announced that monetary policy would focus on monetary aggregates, with consideration of interest rates relegated to second place. A significant effect of this policy change on bond risk premia is demonstrated by Barrett, Heuson, and Kolb [1] and a significant effect on Treasury bond option premia is shown by Jordan, Seale, and Barnhill [12]. The same policy change is examined in the present study and is shown to have a significant impact on sinking fund preferred stock.…”
Section: Preferred Stock—with and Without Sinking Fundssupporting
confidence: 64%
“…Barrett, Heuson, and Kolb [1] cite additional factors impacting the sinking fund effect. They examine three test variables: (1) the intrinsic value of the option to call for the sinking fund requirement at par or market; (2) the striking price effect of ability to call at par or above par; and (3) the effective maturity. Their study includes a variable to control for the effect of a change in monetary policy.…”
Section: Preferred Stock-with and Without Sinking Fundsmentioning
confidence: 99%
See 3 more Smart Citations